2010
DOI: 10.1097/fpc.0b013e32833d8cf5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in type I and II inosine monophosphate dehydrogenase genes and association with clinical outcome in patients on mycophenolate mofetil

Abstract: IMPDH II genotyping may not improve MPA treatment outcome over the first year post-transplantation, in contrast to MPA and calcineurine inhibitor therapeutic drug monitoring and IMPDH I genotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 34 publications
0
36
2
1
Order By: Relevance
“…The biological significance of this finding remains to be elucidated. In our analysis we could not confirm any influence of the six SNPs under observation on IMPDH activity, but this lack of association may be due to the relatively small number of paediatric subjects studied compared with previous reports in adults [15][16][17]19].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The biological significance of this finding remains to be elucidated. In our analysis we could not confirm any influence of the six SNPs under observation on IMPDH activity, but this lack of association may be due to the relatively small number of paediatric subjects studied compared with previous reports in adults [15][16][17]19].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study we analysed seven relevant SNPs of the IMPDH1 and IMPDH2 gene regarding their respective frequency and association with IMPDH activity. Previous studies have observed associations between various IMPDH gene polymorphisms and both IMPDH activity [15,18] and the risk of acute rejection episodes [16,17,19], although data for the latter finding are conflicting [16,19]. Interestingly, we observed in children with ESRD a higher frequency of heterozygous carriers of the IMPDH2 variant rs11706052 than in healthy children or in adults with ESRD [17,19].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The relationship between genetic polymorphisms in type I and type II IMPDH and clinical events was examined in two large studies involving kidney transplant recipients [95] . It was observed that a polymorphism in the IMPDH I gene was associated with a lower risk of acute rejection and leukopenia in the first year after the transplantation.…”
Section: Specific Pharmacodynamic Biomarkers Enzymes As a Pharmacologmentioning
confidence: 99%